Training and pedagogical practices in the teaching of reading multimodal texts for spanish language students - Silva , Denise Pereira da; Trinchão, Gláucia Maria Costa; Souza , Suely dos Santos (Seven Editora, 2023)
Since the Paleolithic period the image is present in the history of humanity, are the cave paintings the confirmation of such a statement. Therefore, it is possible to affirm that, like writing, the image is an important resource for the communication of ideas and feelings, for the records of memory, experiences, memories of the past, actions of the present, or desires for the future, constituting itself as one of the multiple forms of language. DOI:https://doi.org/10.56238/alookdevelopv1-156